The impact of continuous integration on other software development practices: A large-scale empirical study - Yangyang Zhao; Serebrenik, Alexander; Yuming Zhou; Filkov, Vladimir; Vasilescu, Bogdan (2017 32nd IEEE/ACM International Conference on Automated Software Engineering (ASE), 2017)
Continuous Integration (CI) has become a disruptive innovation in software development: with proper tool support and adoption, positive effects have been demonstrated for pull request throughput and scaling up of project sizes. As any other innovation, adopting CI implies adapting existing practices in order to take full advantage of its potential, and "best practices" to that end have been proposed. Here we study the adaptation and evolution of code writing and submission, issue and pull request closing, and testing practices as TRAVIS CI is adopted by hundreds of established projects on GITHUB. To help essentialize the quantitative results, we also survey a sample of GITHUB developers about their experiences with adopting TRAVIS CI. Our findings suggest a more nuanced picture of how GITHUB teams are adapting to, and benefiting from, continuous integration technology than suggested by prior work.